(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to find out (the effectiveness of the learning stations strategy in the acquisition of mathematical concepts by the second intermediate grade female students). A female student, the learning stations strategy was applied to the two research groups (experimental and control). Teaching plans were developed for both groups. A test was built in acquiring mathematical concepts according to Badawi classification (concept definition, concept recognition, concept application) consisting of (45) items. It was presented to a group of experts and specialists in the methods of teaching mathematics, and after applying the test to the two groups, it showed Results There is a statistically significant difference between the two groups and in favor of the experimental group. The research concluded that the learning stations strategy has an important role in the students’ acquisition of mathematical concepts. It recommends the use of this strategy in secondary schools. The research also suggested conducting a similar study on other dependent variables such as multiple intelligences, thinking of all kinds, and problem-solving skills.